The Importance of Facilities Services to Enhance Service Quality in Higher Education Institution - ., Suharto; Suparningsih, Budi; Hasbullah, Amilia; Zahari Wan Yusoff, Wan (International Journal of Engineering and Technology, 2019)
Service quality in Higher Education Institution (HEI) faces challenging phase in accordance with economic competition around the globe. Educational facilities services are one of prerequisites factor as HEI to perform academic activities which mainly measured in service quality. However, the discourse of educational facilities significance to underpinning HEI activities is still lacking. Service quality required profound dimensions in enhancing the service excellence provided by HEI. Therefore, this paper seeks to uncover facilities significant toward service quality in HEI. Preliminary study was taken to obtain the views and perception of academicians in Indonesian Public Higher Education Institution toward the importance of facilities services to enhance service quality. The data were collected through survey distribution. The findings revealed that academician considered that facilities services enhance service quality in HEI.Â Â